Hate Speech and Discursive Critique/Discourse Analysis as Critique. Contrastive Analysis of the Media Discourses on Migration in Poland and Germany at the Beginning of the Refugee Crisis in Europe - Czachur, Waldemar; Smykała, Marta (Hassrede – ein multidimensionales Phänomen im interdisziplinären Vergleich, 2020)
The contribution aims to discuss the results of a contrastive analysis of the media discourses on migration in Poland and Germany, which took place at the beginning of the so-called refugee crisis, against the background of the phenomenon of hate speech discursive critique/discourse analysis as critique. The analysis focuses on the discourses in the period August to October 2015 in the magazines Wprost, Gazeta Polska, Polityka and Die Zeit.